FATHER-SON RELATIONSHIP IN FATHERLAND - BAĞIRLAR, Belgin (NEW ERA INTERNATIONAL JOURNAL OF INTERDISCIPLINARY SOCIAL RESEARCHES, 2021)
This study aims to probe, in depth, the father-son dynamic between the characters of contemporary English playwright Simon Stephens’s, Karl Hyde’s and Scott Graham’s Fatherland (2017). Since the nineteenth century, British literature and drama have handled the father-son relationship multiple times. This study in particular will be framed within psychologist Sigmund Freud’s Oedipus complex on the role of the father in a child’s development. The characters of Fatherland are all male adults: Scott, Karl, and Simon. While preparing for a television show on fatherhood, they set out to find inspiration in real stories and ultimately decide upon incorporating those stories into their programme. They interview with their friends, and ask them to reminisce about their fathers and fatherhood. Each character has different experiences, and reveals pieces of themselves as they talk about them. Some act towards their children as their own fathers had acted towards them; others find themselves acting to the contrary. In this sense, Stephens, Hyde, and Graham awaken their audience’s sense of awareness towards this [father-son] interrelationship by looking at it from various vantage points.